A review on speaking and listening learning for L2 learners - Chen Fang (SHS Web of Conferences, 2024)
A critical synthesis of four studies which was divided into four main sub-groups was conducted trying to explain the issues of second-language learner and provided suggestions for language teachers to effectively improve the integrated skills of students.